Comparative event-based rainfall analysis - Islam, Sheikh Md. Darul; Bogardi, Janos J.; Huynh, Ngoc Phien; Nielsen, Steen Asger; German Academic Exchange Service( DAAD ) (Bangkok : Asian Institute of Technology, 1987)
Event-based stochastic rainfall analysis technique has been proven successful in semi-arid climatic condition, where the rainfall is commonly summer type convective precipitation. This study deals with the transfer of an event-based rainfall analysis technique to the tropical humid climat e as this technique can also be applied for long lasting rainfall events i.e. for general frontal storms. This trans fer process includes the determination of event-based rainfall characteristics of the studied duration as well as synthetic data generation for planning purposes. Bangladesh normally experiences a tropical humid climate in its seasonal variation. Daily rainfall data of six rainfall recording stations in the central region of Bangladesh are coll ected for this study from the Hydrology Directorate of Bangladesh Water Development Board (BWDB), Dhaka. With the help of existing procedure developed for s emi-arid climatic conditions with certain modifications, the event-based characteristics such as number of events, event durations, rainfall depth, interevent time, etc. were determined for the studied area. Kolmogorov-Smirnov test was considered for goodness of fit indices at the 5% significance level. Event-based characteristics along with the generated synthetic data series showed an acceptable response in this case study though there were some works left still to be accomplished in transferring the method. It can be stated that the event-based technique developed for semi-arid condition can also be applied in humid tropical climate with certain modifications depending on the climatic conditions of the study area concerned.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Rain and rainfall -- Mathematical models